FINE EPOCA BERLUSCONI – L’AMARO CALICE DELLA POLITICA THE END OF THE EPOCH OF BERLUSCONI – BITTER FLAVOUR OF THE POLITICS. LINGUISTIC GAININGS - Lakhtionova, Kateryna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
The article is devoted to the phenomenon of Berlusconi, his political activity in the Parliament of the Italian Republic from the perspective of linguistic gainings, in other words, considering the enrichment of italian political vocabulary within the political life of Italy, appearance of neologisms, idioms and other derivatives, related with this odious man. We deliberately translate “calice” as “flavour” instead of “cup”, to highlight the danger of the usurpation of power, since the new lexicon, which appeared during the ministry of Berlusconi, almost always carries a negative connotation. With the development of his political activity, on each stage of his lightning fast career new lexicon, related with his personality, appears. _____________ References: • Santarelli, Enzo. Profilo del berlusconismo (Roma: Datanews Editrice, 2002), 76 p. • Montanelli, Indro. Lo stato sono io (Roma: Il Giornale, 2002). • Pranfaglia, Nicola. Se questo è un regime (L’unità, 27 febbraio 2002). • Bertinotti, Fausto. Il peggio si è compiuto (Liberazione, febbraio 2002). • Styshov, Oleksandr. Ukrai’ns’ka leksyka kincja HH stolittja (na materiali zasobiv masovoi’ informacii’) (Kyi’v, “Pugach”, 2005), 388 s.